UNVEILING PROGRESS: THE IMPLEMENTATION OF REGIONAL REGULATION FOR WOMEN AND CHILD PROTECTION - Pua, Yunistia Warda; Mozin, Sri Yulianty; Tohopi, Rustam (Universitas Negeri Gorontalo, 2024)
The purpose of this research is to describe the Implementation of Government Policy, as stipulated in Regional Regulation No. 7 of 2016 concerning the Protection of Women and Children Against Victims of Violence in Gorontalo City, and seen from indicators (a) Communication, (b) Resources, (c) Disposition/Attitude of Implementers, and (d) Bureaucratic Structure. This research method uses descriptive qualitative. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques through data reduction, data presentation, and conclusions. The findings of the research show that based on the implementation process, this policy has been implemented properly and is in accordance with the provisions of Regional Regulation No. 7 of 2016. However, the lack of effective communication with the community, in this case, socialization to anticipate violence against women and children, is what causes this policy to become less effective. Therefore, there is a need for improvement, namely by holding routine outreach to all levels of society. In addition, judging from the Determinant Factors in the Implementation of the Policy for the Protection of Women and Children Victims of Violence in the City of Gorontalo, it has been implemented properly according to the provisions of Regional Regulation No. 7 of 2016. However, the obstacles are communication with the community and also limited resources. This can be overcome by increasing coordination and collaboration.